The impact of formal education on literacy and numeracy skills in Chilean adults: a comparative analysis with Latin American counterparts - Moncada Nahuelquín, Fernando; Ibáñez Orellana, Romualdo; Kuperman, Victor (Frontiers in Education, 2025)
Chile and other Latin American countries consistently demonstrate the lowest scores in the international surveys of foundational information-processing skills. This paper examines the effect of formal education on the literacy and numeracy performance of Chilean adults and compares this effect with that observed in Latin American countries with similar information-processing skills. Using data from the Programme for the International Assessment of Adult Competencies (PIAAC), we conducted a comparative analysis of literacy and numeracy skills in the Chilean population relative to Mexico, Peru, and Ecuador. Our analysis revealed that, regardless of the years of formal education, the populations of these countries do not achieve a level 3 in literacy and numeracy skills (on PIAAC’s five-level scale), which is considered the minimum requirement for effective participation in today’s technologically-driven economy and society. We also observed that Chileans at higher levels of formal education (with a bachelor’s or higher university degree) are on par with or exceed the literacy and numeracy skills of the best-performing Latin American country, Mexico. Less educated Chileans, however, lag behind education-matched groups of Mexicans and rank with the lowest-performing countries like Peru and Ecuador, in both skills. These findings highlight critical implications for educators and policy-makers in Latin America, particularly concerning educational system effectiveness in developing crucial competencies. The analysis shows the impact of past and ongoing reforms in the Chilean school system and underscores the importance of addressing skill development across all educational levels for personal and professional success in contemporary society.